2017
DOI: 10.1007/s10151-016-1570-z
|View full text |Cite
|
Sign up to set email alerts
|

Transanal total mesorectal excision (TaTME) for rectal cancer: effects on patient-reported quality of life and functional outcome

Abstract: BackgroundTransanal total mesorectal excision (TaTME) has rapidly become an important component of the treatment of rectal cancer surgery. Cohort studies have shown feasibility concerning procedure, specimen quality and morbidity. However, concerns exist about quality of life and ano(neo)rectal function. The aim of this study was to prospectively evaluate quality of life in patients following TaTME for rectal cancer with anastomosis.MethodsConsecutive patients who underwent restorative TaTME surgery for rectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 29 publications
1
85
0
2
Order By: Relevance
“…A study by Pontallier et al [19] reported severe symptoms after both transanal and laparoscopic approaches for low rectal cancer, with major LARS in 82 and 76% of the transanal and standard laparoscopy patients, respectively. A recently published study by Koedam et al reported 33% major LARS in patients after TaTME [20]. While both studies showed significant LARS symptoms after transanal resection, their results cannot be compared because the two studies included different patient groups, with more distal tumors and intersphincteric resections in the Pontallier study [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pontallier et al [19] reported severe symptoms after both transanal and laparoscopic approaches for low rectal cancer, with major LARS in 82 and 76% of the transanal and standard laparoscopy patients, respectively. A recently published study by Koedam et al reported 33% major LARS in patients after TaTME [20]. While both studies showed significant LARS symptoms after transanal resection, their results cannot be compared because the two studies included different patient groups, with more distal tumors and intersphincteric resections in the Pontallier study [19].…”
Section: Discussionmentioning
confidence: 99%
“…Koedam et al [14] assessed the patient-reported quality of life of 30 consecutive patients who underwent TaTME for rectal cancer. Quality of life was assessed by three questionnaires: Overall Quality of Life (EQ-5D-3L), Colorectal Cancer Specific Quality of Life (EORTC: QLQ-C30 and QLQ-CR29) and Anterior Resection Syndrome (LARS) scale.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Előnyként említhe-tő az alacsonyabb végleges colostomaképzési arány [33], a jobb funkcionális mutatók (inkontinencia, vizelési és szexuális funkciók tekintetében) [34], valamint a posztoperatív morbiditási eredmények némi javulása [32,33]. Mivel ezek az eredmények nem randomizált prospektív vizsgálatok különböző sebésztechnikát alkalmazó karjainak összehasonlításából származnak, így magas szintű evidencia helyett csupán jelzésértékű klinikai leletek.…”
Section: Megbeszélésunclassified
“…Műtéti jellemzők, szövődmények, posztoperatív jellemzők [34]. Az életminőségi és funkcionális eredmények kritikus értékelése a TaTME-műtét klinikai helyének hosszú távú megítéléséhez alapvető fontosságú szempontként merül fel.…”
Section: Táblázatunclassified